Asthma and PTSD association: relevant models and a role of IL17AA. (September 2021) - Allgire, E.; McAlees, J.; Lewkowich, I.; Sah, R.
Abstract : Background: Strong genetic and epidemiological evidence supports an asthma-PTSD association, however, contributory immune mediators/mechanisms are unclear. Here, we examined a direct role of severe asthma associated Th17/ IL-17A in regulating PTSD-relevant behaviors using mouse aeroallergen house dust mite (HDM) models. Methods: 3 strategies were used: 1) BALBc-C5a receptor treatment that shifts Th2 mild asthma phenotype to Th17/IL17a expansion; 2) IL-17a receptor knockout mice and 3) sufficiency testing with intracerebroventricular (ICV) administration of recombinant IL17a effects on behavior. Fear conditioning and extinction, maze exploration and social behaviors were assessed. Results: Absence of IL-17 signaling attenuated HDM effects on fear extinction while induction of Th17/IL-17 in the BALBc/anti-C5aR1 treated mice resulted in compromised fear extinction. ICV IL-17a promoted an anxiogenic phenotype and impaired social behaviors. Preliminary evidence suggests a role of cortical mechanisms (under investigation). Conclusion: Overall, our work highlights severe asthma inflammatory mediator IL17a in regulating PTSD-relevant behaviors. Beyond asthma-PTSD, our findings have relevant implications for other pulmonary (e.g. COVID-19) and autoimmune inflammatory conditions and PTSD risk.